Pendampingan Guru Pendidikan Anak Usia Dini dalam Penilaian Status Gizi Anak Usia Prasekolah: Assistance for Early Childhood Education Teachers in Assessing Nutritional Status of Preschool-Aged Children - Pondagitan, Alpinia Shinta; Lapian, Lady Galatia; Sanggelorang, Yulianty; Herlambang, Hendra Agung (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Children's cognitive, emotional, social, motoric, and language development needs to be supported with healthy growth, especially during the preschool age period. To maintain good health from a preschool age, a person must improve their level of health by controlling factors that can pose a negative risk to their own well-being. Teachers play a crucial role in the school structure as agents of change. A change agent is an individual who possesses the skills and abilities to stimulate, facilitate, and coordinate change. Anthropometric measurements are a method of assessing nutritional status that involves evaluating the dimensions and composition of the human body, including body weight and height. Monitoring the growth of early childhood through routine anthropometric measurements every month and determining nutritional status using graphs or growth curves established by the Government is crucial because it is one of the efforts to prevent stunting. This mentoring activity consists of three stages: the preparation stage, the implementation stage, and the evaluation stage. The target audience of this activity is teachers in the Early Childhood Education (PAUD) environment. The activity was conducted at Alwildan Kindergarten, Manado City, and RA Darul Faizin, Manado City, with a total of 10 participants. Pretest questionnaire results showed that only 30% of participants demonstrated good knowledge, with a score of 80 or higher. In contrast, the posttest questionnaire results indicated that all participants demonstrated good knowledge about nutrition and techniques for measuring weight and height, with a score of 80 or higher.